1993
DOI: 10.1109/65.224055
|View full text |Cite
|
Sign up to set email alerts
|

Giving applications access to Gb/s networking

Abstract: Network fabrics with Gigabit per second (Gbps) bandwidths are available today, but these bandwidths are not yet available to applications. The difficulties lie in the hardware and software architecture through which application data travels between the network and host memory. The hardware portion of the architecture is often called a host interface and the remainder of the protocol stack is implemented in host software.In this paper, we outline a variety of approaches to the architecture of such systems, exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(18 citation statements)
references
References 24 publications
(20 reference statements)
1
17
0
Order By: Relevance
“…Our cost-breakdown for the various costs, summarized in Figure 1, shows that over 20% of the processing time is spent copying data over these two buses. Such findings have been reported in the past for other systems [10], [11], [12], [13], and are by no means limited to cryptography or network I/O.…”
Section: Network Cryptographysupporting
confidence: 60%
See 1 more Smart Citation
“…Our cost-breakdown for the various costs, summarized in Figure 1, shows that over 20% of the processing time is spent copying data over these two buses. Such findings have been reported in the past for other systems [10], [11], [12], [13], and are by no means limited to cryptography or network I/O.…”
Section: Network Cryptographysupporting
confidence: 60%
“…[15] began examining cryptographic subsystem issues in the context of securing high-speed networks, and observed that the busattached cards would be limited by bus-sharing with a network adapter on systems with a single I/O bus. A second issue pointed out in that time frame [16] was the cost of system calls, and a third [10], [11], [12], [13] the cost of buffer copying. These issues are still with us, and continue to require aggressive design to reduce their impacts.…”
Section: Related Workmentioning
confidence: 99%
“…First, such numbers often say more about the traffic capture (e.g. polling or interruptdriven) than about the processing [ST93]. Second, we are really interested in how the Corral compares to typical ANs and this concerns primarily the nature of code execution: in-kernel native code versus interpreted code in userspace.…”
Section: Resultsmentioning
confidence: 99%
“…The original FLAME architecture interacted with the network interface exclusively through interrupts. As others have noted [15,22], under high rates of incoming network traffic, interrupt handling can degrade performance. More recent versions of FLAME poll the network interface card (NIC) to read packets to avoid performance degradation.…”
Section: Overview Of the Flame Architecturementioning
confidence: 99%